2004
DOI: 10.1002/jnr.20289
|View full text |Cite
|
Sign up to set email alerts
|

NAD+ as a metabolic link between DNA damage and cell death

Abstract: DNA damage occurs in ischemia, excitotoxicity, inflammation, and other disorders that affect the central nervous system (CNS). Extensive DNA damage triggers cell death and in the mature CNS, this occurs primarily through activation of the poly(ADP-ribose) polymerase-1 (PARP-1) cell death pathway. PARP-1 is an abundant nuclear enzyme that, when activated by DNA damage, consumes nicotinamide adenine dinucleotide (NAD)+ to form poly(ADP-ribose) on acceptor proteins. The mechanisms by which PARP-1 activation leads… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
154
0
4

Year Published

2004
2004
2012
2012

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 265 publications
(161 citation statements)
references
References 53 publications
3
154
0
4
Order By: Relevance
“…In settings where glucose is the chief metabolic substrate, this leads to mitochondrial dysfunction and cell death (Alano et al, 2004;Ying et al, 2003;Zong et al, 2004). Interestingly, repletion of NAD + after PARP-1 activation has been shown to restore glycolytic capacity and prevent cell death (Ying et al, 2003(Ying et al, , 2005 in primary neuronal cultures. Similarly, providing nonglucose substrates such as pyruvate and a-ketoglutarate that can be metabolized without the need for cytosolic NAD + also preserves cell viability, even when delivered hours after PARP-1 activation (Alano et al, 2004;Ying et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…In settings where glucose is the chief metabolic substrate, this leads to mitochondrial dysfunction and cell death (Alano et al, 2004;Ying et al, 2003;Zong et al, 2004). Interestingly, repletion of NAD + after PARP-1 activation has been shown to restore glycolytic capacity and prevent cell death (Ying et al, 2003(Ying et al, , 2005 in primary neuronal cultures. Similarly, providing nonglucose substrates such as pyruvate and a-ketoglutarate that can be metabolized without the need for cytosolic NAD + also preserves cell viability, even when delivered hours after PARP-1 activation (Alano et al, 2004;Ying et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…However, the increased presence of these pathway intermediates in nuclear DNA resulting from increased MPG activity proved to be cytotoxic in astrocytes treated with MNU. One possible mechanism that could be responsible for the increase in cell killing is the activation of Poly-ADP Ribose Polymerase (PARP) with the subsequent depletion of NAD within the cells (Ying et al, 2005). PARP is abundant in the nucleus and is activated by SSB, which are generated at a 4-fold greater rate in NucMPG astrocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, NAD + restoration adds to energy depletion, because four ATP molecules are required to resynthesize one NAD + (Zhang et al, 1994). The futile-cycle hypothesis is supported by results of monolayer neuron and astrocyte cell culture experiments (Ying et al, 2005(Ying et al, , 2002, which found that PARP hyperactivation by N-methyl-N-nitrosoguanidine or H 2 O 2 led to cytosolic NAD + depletion, glycolytic arrest, and cell death from energy failure. More significantly, cell death in those studies was prevented or reversed by administration of PARP inhibitors or tricarboxylic acid cycle (TCA) substrates such as pyruvate, glutamine, and a-ketoglutarate.…”
Section: Introductionmentioning
confidence: 96%